2000
DOI: 10.1111/j.1572-0241.2000.03347.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Consumption Upon The Gastrointestinal Tract

Abstract: Regardless of the type and dose of beverage involved, alcohol facilitates the development of gastroesophageal reflux disease by reducing the pressure of the lower esophageal sphincter and esophageal motility. Fermented and nondistilled alcoholic beverages increase gastrin levels and acid secretion. Succinic and maleic acid contained in certain alcoholic drinks also stimulate acid secretion. Low alcohol doses accelerate gastric emptying, whereas high doses delay emptying and slow bowel motility. Alcohol facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(107 citation statements)
references
References 75 publications
(59 reference statements)
2
104
0
1
Order By: Relevance
“…However, relatively little attention has been paid to its actions within the stomach. Nevertheless, studies demonstrated that alcohol abuse is associated with development of gastric diseases such as gastritis, gastric peptic ulcer disease, and even gastric cancer [22]. Alcohol stimulates acute gastritis as a result of direct mucosal damages that are further aggravated by other important risk factors such as nonsteroidal antiinflammatory drugs (NSAIDs), acid, Helicobacter pylori infection, and physiological stress [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively little attention has been paid to its actions within the stomach. Nevertheless, studies demonstrated that alcohol abuse is associated with development of gastric diseases such as gastritis, gastric peptic ulcer disease, and even gastric cancer [22]. Alcohol stimulates acute gastritis as a result of direct mucosal damages that are further aggravated by other important risk factors such as nonsteroidal antiinflammatory drugs (NSAIDs), acid, Helicobacter pylori infection, and physiological stress [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, no association was observed with excessive alcohol consumption. Epidemiological studies suggest that alcohol plays a fundamental role in the development of gastrointestinal diseases such as peptic ulcer and gastric cancer since it causes gastric mucosal injuries and stimulates parietal cells to produce gastric acid, in addition to its synergistic action with smoking (5,29) . Inadequate dietary habits such as excess intake of salt, preservatives and smoked produced, as well as diets poor in vegetable and fruits, are also strongly associated with the development of gastric cancer (24,28) .…”
Section: Discussionmentioning
confidence: 99%
“…In 1966, DiLuzio was the first to characterize lipid peroxidation following chronic exposure to alcohol [3]. Because alcoholics may receive up to 50% of their total daily calories from ethanol, it is not surprising that this high degree of dietary substitution leads to nutritional deficiencies (see section on gut-liver axis and cytokine signaling, below) via this route and via malabsorption [4,5]. The net effect is that alcoholics often have lower levels of key antioxidant molecules [6].…”
Section: Mechanisms Of Injury and Potential Therapies Oxidative Stressmentioning
confidence: 99%